Improvement of hollow cylinders on the conversion of coal mine methane to hydrogen in packed bed burner. (3rd September 2021) - Zhu, Huiwei; Dai, Huaming; Song, Ziwei; Wang, Xinyi; Wang, Zhiqiang; Dai, Hongchao; He, Song
Abstract: Coal mine methane (CMM) combustion in the porous media burner (PMB) of boiler system contributes to the simultaneous production of hydrogen and heat, and the hydrogen can be used as the main raw materials for solid oxide fuel cell (SOFC). In this study, the double-layer burners were built by filling the downstream with the hollow cylinders of different sizes and pore numbers due to the high porosity of hollow-structure units compared with the common packed bed of pellets. The distributions of temperature, species concentration and reforming efficiency were obtained on the consideration of operating condition and preheating temperature. Results shows that the reforming efficiency of the 10-6-10 mm cylinder burner was optimal in all one-pore cylinder burners with the highest concentration of 12.3% (H2 ) and 8.8% (CO). As for the packed bed of 8 mm cylinders, the four-pore cylinder burner showed the highest peak temperature and maximum yields of hydrogen. With the increasing of preheating temperature, the stabilization time of the flame propagating decreased. Moreover, the peak temperature and reforming efficiency increased with the increasing of the inlet velocity and the largest efficiency of 54.2% appeared at the velocity of 18 cm/s in the 10 mm cylinder burner. Highlights: The hollow-structured units are packed in the downstream section of the double-layer burner. The hollow alumina cylinders with different sizes and pore number were designed. The temperature and species concentration were measured with different operating conditions. The time of flame reaching to stabilization decreased with the increasing of preheating temperature.